A dimensão geográfica e o modo de produção de um destino como fatores de desenvolvimento turístico - Caetano, Jean Gilberto (Universidade do Vale do Rio dos Sinos, 2018)
Given the relevance and attention that tourist destinations have aroused in recent research and taking into account the possibilities that a territory or place has to leverage tourism from its resources, the present study aims to identify how the geographic dimension and the way of a tourist destination contribute to its development. The study was based on the integrative destination model (PEARCE, 2014), based on an exploratory and descriptive approach, of a qualitative analysis method based on a single case study. Secondary data collection was done through documentary analysis and the primary data were obtained from individual interviews, using semi-structured interview scripts. The analysis of the data was based on the content analysis and the unit of analysis was based on the Araucarias Circuit, formed by the cities of Campo Alegre, Corupá, Rio Negrinho and São Bento do Sul, north of Santa Catarina. The evidence pointed to elements identified in the destination, which were analyzed and approximated to the geographic dimensions and mode of production. Four relationships were then made between the elements. As a result of the analysis, the R1 relationship is based on the use of existing natural, cultural and attractive resources and the presence of an organizational structure. The R2 relationship is characterized by the link between local actors, the improvement of processes and the tourism trade, the management group and the community culture. The R3 Ratio is identified in the Araucarias Circuit and deals with the connection between border delimitation, the management group, public power and community culture. And the R4 relationship is evidenced by the realization of events to promote the tourism product and with the mutual help of all city halls and managers, by the joint work between the tourism departments, in an integrated and regional way. From these relations it can be affirmed that, for a tourist destination to become recognized, it is necessary more than beautiful natural attractions. It is necessary a strong relationship between geographic and organizational elements, that is, people and that they are articulated and engaged, that take advantage of the existing resources in the territory, that create an attractive tourist product and that have as a greater objective the systemic success of all those involved in the tourist destination.
Keywords: Destino turístico; Dimensão geográfica; Modo de produção; Tourist destination; Geographic dimension; Production mode; ACCNPQ::Ciências Sociais Aplicadas::Administração